Polyacrylonitrile–lithium bis(oxalato) borate polymer electrolyte for electrical double layer capacitors - Arof, Abdul Kariem; Shuhaimi, N.E.A.; Amirudin, S.; Kufian, M.Z.; Woo, H.J.; Careem, M.A. (John Wiley & Sons, 2014)
Lithium ion conducting polymer electrolytes based on polyacrylonitrile (PAN) and lithium bis(oxalato)borate (LiBOB) have been prepared and characterized. The polymer electrolytes having PAN:LiBOB weight ratios of 90:10, 80:20, 70:30, 60:40 and 50:50 were prepared using dimethylformamide as solvent. The electrolyte having the composition 50 wt.% PAN–50 wt.% LiBOB shows the highest room temperature conductivity of 2.55 × 10−5 S cm−1. This sample demonstrated a lithium ion transference number of 0.25 and a breakdown voltage of 1.6 V. The highest conducting electrolyte was then sandwiched between two symmetrical carbon electrodes to fabricate an electrical double layer capacitor (EDLC). The EDLCs were characterized using impedance measurement, cyclic voltammetry (CV) and galvanostatic charge–discharge tests. The capacitance obtained from impedance measurement is about 35 F g−1 at frequency 10 mHz. From CV, the capacitance is calculated to be 24 F g−1 at 10 mV s−1 scan rate. The discharge capacitance of the EDLCs is determined in the range from 22 to 10 F g−1 at corresponding discharge currents from 0.2 to 1.5 mA, respectively. This also corresponds to a specific energy from 3.01 to 1.47 W h kg−1 and a specific power from 380 to 474 W kg−1, respectively.